Influence of halloysite nanotubes on physical and mechanical properties of cellulose fibres reinforced vinyl ester composites - Alhuthali, A.M.; Low, It Meng (Sage Publications Ltd., 2013)
Natural fibres are generally added to polymer matrix composites to produce materials with the desirable mechanical properties of higher specific strength and higher specific modulus while at the same time to maintain a low density and low cost. The physical and mechanical properties of polymer composites can be enhanced through the addition of nanofillers such as halloysite nanotubes. This article describes the fabrication of vinyl ester eco-composites and eco-nanocomposites and characterizes these samples in terms of water absorption, mechanical and thermal properties. Weight gain test and Fourier transform infrared analysis indicated that 5% halloysite nanotube addition gave favourable reduction in the water absorption and increased the fibre–matrix adhesion leading to improved strength properties in the eco-nanocomposites. However, halloysite nanotube addition resulted in reduced toughness but improved thermal stability.